Are adolescent self-harm services, during and after presentation to hospital, reflective of NICE Guidelines? A Critical Review - Chapman, Jennifer (2011)
Aim: To conduct a critical review of the literature regarding adolescent self-harm services in England and Wales, with a specific focus on presentation to A&E, hospital stay, and the provision of follow-up care in order to determine if practice reflects NICE guidelines. The review question is therefore; are adolescent self-harm services, during and after presentation to hospital, reflective of NICE Guidelines? Background: The typical onset of self-harm occurs during adolescence, with 1 in 10 young people self-harming at some point (Nixon and Heath, 2009). It is a common reason for adolescents to present to hospital (Hawton, Rodham and Evans, 2002) and would appear to be on the increase (Young et al., 2007). Despite this, however, adolescent self-harm services remain inconsistent and ineffective. Methods: 5 electronic databases including ASSIA, BNI, CINAHL, MEDLINE and PsycINFO, were investigated using identified search terms relating to self-harm and adolescence. Incremental searching was also conducted. This identified 9 relevant studies, the quality of which were then assessed using the general critical appraisal tool developed by Callaghan and Crawford (2009) and given a clear weighting using a dichotomous rating scale. Findings: Common themes identified within NICE clinical guideline 16 were used in the identification of similar themes within the literature. These included respect, training, treatment, assessment and follow-up care. It was found that healthcare professionals exhibit negative attitudes towards young people who self-harm. Adolescents experience inconsistent treatment in hospital. Half of those who present to hospital do not receive psychosocial assessment and an even smaller proportion receive appropriate follow-up care. Conclusion: This review of the literature determined that adolescent self-harm services do not reflect NICE clinical guideline 16. Implications for practice include improved training specific to self-harm for healthcare staff that come into contact with self-harming adolescents. Further research of adolescents‟ experiences of self-harm services is required in order to determine improvements necessary in these services.